Student Loan Debt for Borrowers of Color: A Policy Afterthought? (Higher Education Politics and Economics, 2023)
Levels of student loan debt in the United States are increasing exponentially every year, directly affecting the ability of millions to live a comfortable life. Student loan debt levels are an acute issue for borrowers of color, as they more often need federal loans to attend institutions of higher education in comparison to their white peers. This qualitative study focuses on this issue through the lens of Critical Whiteness Studies, using a Critical Discourse Analysis to better understand what messages policymakers create for borrowers of color. Discourse studied in this analysis includes the text of the Public Service Loan Forgiveness Program and all proposed amendments, personal Senate websites of all committee members, and newsletters published by the Senate Health, Education, Labor, and Pensions committee in the 117th Congress. The findings of this study show uneven support for borrowers of color, largely divided under political party lines.